Substrate specificity of branched chain amino acid aminotransferases: The substitution of glycine to serine in the active site determines the substrate specificity for α-ketoglutarate - Sutter, Jan-Moritz; Mitchell, Daniel E.; Schmidt, Marcel; Isupov, Michail N.; Littlechild, Jennifer A.; Schönheit, Peter (Frontiers in Catalysis, 2022)
A branched chain aminotransferase from Thermoproteus tenax has been identified, cloned, over-expressed and biochemically characterised. A molecular modelling approach has been used to predict the 3D structure allowing its comparison with other related enzymes. This enzyme has high similarity to a previously characterised aminotransferase from Thermoproteus uzoniensis however its substrate specificity shows key differences towards the substrate α-ketoglutarate. Examination of the active sites of the two related enzymes reveals a single amino acid substitution of a glycine residue to a serine residue which could be responsible for this difference. When the mutation of Gly104 in Thermoproteus tenax was mutated to a serine residue and the resultant enzyme characterised, this single amino acid change resulted in a dramatic reduction in activity towards α-ketoglutarate. Structural comparisons between the two related Thermoproteus enzymes and another branched chain aminotransferase from Geoglobus acetivorans has revealed that the serine residue affects the flexibility of a key loop involved in catalysis. This subtle difference has provided further insight into our understanding of the substrate specificity of these industrially important enzymes.